Portuguese Version of COVID-19 Perceived Risk Scale and COVID-19 Phobia Scale: psychometric properties - Leite, Ângela (2021)
The COVID-19 pandemic scenario has a psychological impact on individuals and society. A higher level of perceived risk concerning COVID-19 has been found when compared to other potential health threats. A misperception of risk in contrast with the real risk may lead people to develop disruptive cognitive, affective, or behavioral responses to the COVID-19 pandemic, namely, coronaphobia. Validated instruments are needed to evaluate such responses. This work aims to validate the COVID-19 Perceived Risk Scale (C19PRS) and the COVID-19 Phobia Scale (C19PS) in the Portuguese population. The two scales were translated from English to Portuguese using the back-translation technique. The cultural adaptation was framed in the context of establishing the validity and reliability of the instruments. In two studies, C19PRS and C19PS were validated for the adult Portuguese population (N = 1122; women = 725 (64.6%); mean age of 31.91 years old) through exploratory factorial analysis, followed by a confirmatory factorial analysis. Convergent validity was calculated by composite reliability (CR) and average variance extracted (AVE) values. Discriminant validity was assessed by square roots of the AVE values and their comparison with the C19PRS and C19PS dimensions’ cross-correlations. Both C19PRS and C19PS present a good adjustment model and solid reliability and validity and have significant correlations with fear of COVID-19 and COVID-19 anxiety scales.